Asymptotic performance of M-ary signals on Rician fading diversity channels / by Hongwei Zhang. - Zhang, Hongwei (My University, 2007)
In this thesis, we will study the average symbol error rate of M-ary signals on wireless Rician fading channels at high average signal-to-noise ratio (SNR) in both single-carrier and multicarrier orthogonal frequency division multiplexing (OFDM) systems. In the system discussed, diversity reception with maximal ratio combining (MRC) and equal gain combining (EGC) is adopted. A general theorem relates the asymptotic error rate to the multidimensional integral of the conditional error probability is presented. Two other theorems are presented for the special cases where the conditional error probability is function of the sum of received SNR's and the sum of received amplitudes corresponding to the cases using MRC diversity and EGC diversity respectively. Then theorems are provided to analyze the asymptotic error rate performance of M-ary signals including M-ary phase-shift keying (MPSK), M-ary pulse amplitude modulation (MPAM), and M-ary quadrature amplitude modulation (MQAM) signals in both single-carrier and multicarrier OFDM systems.
Keywords: Orthogonal frequency division multiplexing; Adaptive signal processing; Phase shift keying